2011
DOI: 10.3109/08037051.2011.558332
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of renal artery stenosis using both resting pressures ratio and fractional flow reserve – Relationship to angiography and ultrasonography

Abstract: BACKGROUND. Clinical benefit from renal artery revascularization remains controversial, probably because of inaccurate stenosis severity assessment. Objective. The aim of the study was to evaluate resting translesional pressures ratio and renal fractional flow reserve (rFFR) in relation to angiography and Doppler duplex ultrasonography in patients with at least moderate renal artery stenosis (RAS). METHODS. 44 hypertensive patients (48% of males, mean age 65 years) with at least moderate RAS were investigated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Moreover, advanced arteriosclerosis in intrarenal arteries at an advanced stage of diabetic nephropathy may contribute to the increase in the RI 48 . Therefore, renal hypertrophy and the increase in the RI could represent two different phases: renal enlargement is a prealbuminuric reversible step of renal involvement in diabetes mellitus, whereas the RI increase indicates the progression of disease with renal scarring, which precedes the appearance of albuminuria 49 52 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, advanced arteriosclerosis in intrarenal arteries at an advanced stage of diabetic nephropathy may contribute to the increase in the RI 48 . Therefore, renal hypertrophy and the increase in the RI could represent two different phases: renal enlargement is a prealbuminuric reversible step of renal involvement in diabetes mellitus, whereas the RI increase indicates the progression of disease with renal scarring, which precedes the appearance of albuminuria 49 52 …”
Section: Discussionmentioning
confidence: 99%
“…For the fi rst time, a signifi cant correlation was found between a transstenotic pressure gradient ratio of < 0.90 as determined by pressure wire and a decrease in intrarenal RI < 0.05 when inducing RAS after stent placement by gradually infl ating a balloon catheter, as described by De Bruyne et al [15]. Kadziela et al [19] found that the mean transstenotic pressure gradient ratio and fractional fl ow reserve (FFR) strongly correlate with angiography and less so with ultrasound parameters. The best accuracy cut-off values for predicting severe RAS were a ratio of 0.93 and an FFR of 0.80.…”
Section: Discussionmentioning
confidence: 72%
“…More recent PTA studies often combine this definition with additional haemodynamic measurements, e.g. a systolic pressure gradient [34], measurement of the fractional flow reserve [35] or use a more strict cut-point of >70%. In this study we used the definition of ARAS as defined >50%, in accordance with the STAR study [19].…”
Section: Discussionmentioning
confidence: 99%